Offshore financial services sector : legal policy issues development : a legal defence - Antoine, Rosemarie (2001)
Attempts to demonstrate that while legimate concerns may be raised in relation to the sector, many of the current allegations, though posed as valid legal objections, are coloured by political and economic overtones. Suggests that it is an opportune moment to underline accurately the legal principles underpinning the sector and mount an appropriate legal defence.